The Role of Munich Analogy in United States Foreign Policy and Latin America's Cold War - Prokop, Michal (2016)
The Munich analogy has been one of the most influential paradigms, which framed the United States strategic thinking in terms of use of force since 1945. The 1930s negative experience of appeasement traditionally served as a vehicle of rationalizing open and covert interventions, which allegedly aimed to stop the repetition of World War II scenario. The application of the historical reasoning in the US-Latin American relations since the 1950s contributed to the creation of the Munich syndrome in US foreign policy. This perception of threats led the American leaders to believe that the political changes in Latin America represented a serious challenge to the national security of the US. This study examines the role of Munich analogy and its relevance in justifying the policies of regime change in four Latin American countries namely Chile the Dominican Republic Grenada and Nicaragua. Due to the historical analogy contribution the indigenous political conflicts within these states were incorporated into dynamic Latin American Cold War. Based on the new available official documents and declassified files this paper offers a new perspective on the significant period of the 20th century international relations, whose consequences can be traced even in the contemporary US politics.